Analysis on the cause and mechanism of color lose of fermented fruit wine rich in anthocyanins - LIANG Shuyan; BAI Weibin; LIU Jiahui; SUN Jianxia (浙江大学学报. 农业与生命科学版, 2021)
Poor color stability is the bottleneck, which restricting the development of fermented fruit wines rich in anthocyanins. In this paper, anthocyanins and their derivatives, which are important factors affecting the color loss of fermented fruit wines, were analyzed, and the physical and chemical methods used at home and abroad to improve the color stability of fruit wine were summarized. This review may provide a certain theoretical basis for the research on the color stability of fruit wine, and promote the development of fruit deep processing industries.